Alocação multicritério de recursos aplicada à construção de portfólios de energia - Lais Claudine Schiavo Gomes (2022)
The Brazilian electricity sector has recently undergone significant changes in terms of its modernization. One of these changes is the expansion of the free electricity market, which aims to make the market more competitive, favoring more participants and also requiring greater investment and better cost and risk management by agents. In managing their energy portfolio, generators face significant challenges, such as the uncertainty of renewable generation and the variability of energy prices. It is important to decide what to do and how to do it, based on the current position of the portfolio: maintain, replace or expand this position, and for this it is desirable to use tools that help in this decision-making process. In this sense, this work presents a method to build and evaluate the energy portfolio of a generator, using a multi-criteria decision-making technique for resource allocation. The work explores the adoption of a criterion that represents the diversity of portfolio assets as a way to mitigate risk, along with the criteria of expected net income and average exposure to the short-term market. Therefore, the application of the multi-criteria approach is interesting in this type of problem. Agents seek to maximize their financial return and reduce their risks, goals that are in conflict with each other, and then robust and harmonious solutions are sought between these goals. The results obtained for two portfolio expansion case studies demonstrate the applicability of the methodology.